Psychosocial stress and major cardiovascular events in patients with stable coronary heart disease. (23rd October 2017) - Hagström, E.; Norlund, F.; Stebbins, A.; Armstrong, P. W.; Chiswell, K.; Granger, C. B.; López‐Sendón, J.; Pella, D.; Soffer, J.; Sy, R.; Wallentin, L.; White, H. D.; et al.
Abstract: Objectives: Assess the risk of ischaemic events associated with psychosocial stress in patients with stable coronary heart disease (CHD). Methods: Psychosocial stress was assessed by a questionnaire in 14 577 patients (median age 65.0, IQR 59, 71; 81.6% males) with stable CHD on optimal secondary preventive therapy in the prospective randomized STABILITY clinical trial. Adjusted Cox regression models were used to assess associations between individual stressors, baseline cardiovascular risk factors and outcomes. Results: After 3.7 years of follow‐up, depressive symptoms, loss of interest and financial stress were associated with increased risk (hazard ratio, 95% confidence interval) of CV death (1.21, 1.09–1.34; 1.15, 1.05–1.27; and 1.19, 1.08–1.30, respectively) and the primary composite end‐point of CV death, nonfatal MI or nonfatal stroke (1.21, 1.13–1.30; 1.19, 1.11–1.27; and 1.17, 1.10–1.24, respectively). Living alone was related to higher risk of CV death (1.68, 1.38–2.05) and the primary composite end‐point (1.28, 1.11–1.48), whereas being married as compared with being widowed, was associated with lower risk of CV death (0.64, 0.49–0.82) and the primary composite end‐point (0.81, 0.67–0.97). Conclusions: Psychosocial stress, such as depressive symptoms, loss of interest, living alone and financial stress, were associated with increased CV mortality in patients with stable CHD despite optimal medical secondary prevention treatment. Secondary prevention of CHD should therefore focus also on psychosocial issues both in clinical management and in future clinical trials.